2010
DOI: 10.1016/j.mechrescom.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a weak breaking tidal bore

Abstract: A tidal bore is a natural and fragile phenomenon, which is of great importance for the ecology of an estuary. The bore development is closely linked with the tidal range and the river mouth shape, and its existence is sensitive to any small change in boundary conditions. Despite their ecological and cultural value, little is known on the flow field, turbulent mixing and sediment motion beneath tidal bores. Indeed, some striking features can be highlighted in two-dimensional simulations, such as large velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 11 publications
1
15
0
1
Order By: Relevance
“…Over the last decade, the hydraulic behaviors of tidal bores have been extensively investigated through field observations [4][5][6], flume experiments [7,8], and numerical modeling [9][10][11]. It is generally accepted that undular bores begin to form with a Froude (F r ) number slightly above 1.…”
mentioning
confidence: 99%
“…Over the last decade, the hydraulic behaviors of tidal bores have been extensively investigated through field observations [4][5][6], flume experiments [7,8], and numerical modeling [9][10][11]. It is generally accepted that undular bores begin to form with a Froude (F r ) number slightly above 1.…”
mentioning
confidence: 99%
“…These were best seen by some sudden and rapid fluctuations of the transverse and vertical velocity data (Fig. 5), while some recent numerical modelling highlighted the production of large turbulent eddies beneath the bore front and their upstream advection behind the bore [24,40]. These vortical structures remained next to the bed as the bore propagated upstream and the presence of these persisting turbulent structures indicated that a great amount of sediment matters was placed in suspension and advected upstream.…”
Section: Turbulent Flow Fieldmentioning
confidence: 83%
“…The turbulent viscosity μ T is calculated with the Mixed Scale model (Sagaut 1998), which has proved its accuracy for geophysical flows (Lubin 2004;Helluy et al 2005;Lubin et al 2006b, Lubin et al 2010a-2010b. Based on the review of Lubin and Caltagirone (2010), we find that the most widely used subgrid scale model is the Smagorinsky model.…”
Section: Governing Equationsmentioning
confidence: 99%